Fatigue and rutting analyses of a pavement structure with expansive soil-rubber (ESR) base stabilized with off-specification fly ash - Budagher, Emily L., author; Carraro, J. Antonio H., advisor; Shackelford, Charles D., committee member; Funk, Loren G., committee member (Colorado State University. Libraries, 2012)
The focus of this study is to analyze through resilient modulus testing and computer simulations the feasibility of an expansive soil-rubber (ESR) mixture stabilized with off-specification fly ash (ESR-FA) as a pavement base layer. Three mixtures were tested in this study, which were expansive soil, ESR, and ESR-FA mixtures. The off-specification fly ash used included a high sulfur content. The ESR mixture consisted of high-plasticity clay blended with 20% 6.7-mm granulated rubber (by weight). The ESR-FA consisted of the same high-plasticity clay blended with 20% 6.7-mm granulated rubber (by weight) and 14% fly ash. All mixtures were tested at a target relative compaction level equal to 95% (±0.5%) of the Standard Proctor maximum dry density. Expansive soil and ESR specimens were subjected to resilient modulus and Poisson's ratio testing immediately after compaction. ESR-FA specimens were allowed to cure for 14 days before being subjected to resilient modulus and Poisson's ratio testing. All specimens were unsaturated during testing. Stiffness changes due to scrap tire rubber addition and fly ash addition were evaluated during resilient modulus testing. Poisson's ratio was determined using axial and radial transducers during unconfined compression testing. Results suggest that the stiffness of the expansive soil specimen is significantly greater than that of the ESR and ESR-FA specimens. However, the stiffness of the ESR-FA specimen is greater than that of the ESR specimen, which makes it a medium between the expansive soil specimen and the ESR specimen.